Penerapan iptek melalui kukerta terintegrasi guna mengakselerasi pengembangan wisata bahari di Kelurahan Kampung Baru, Kecamatan Senapelan, Kota Pekanbaru - Muhammad Fauzi; Eko Prianto; Budijono Budijono; Iskandar Putra; Muhammad Farhan Surez; Zuriati Murni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Kampung Baru is one of the villages in Pekanbaru city that has the potential to develop large marine tourism. Its strategic location on the coast of Siak River and has a cultural reserve